Nilai Pendidikan Megengan Sebagai Wujud Solidaritas Sosial Masyarakat Desa Sudimoro Kecamatan Megaluh Kabupaten Jombang - Salim Ashar (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2022)
This study aims to reveal the educational value of the megengan tradition which has been preserved for generations to date in the Sudimoro village community, Megaluh district, Jombang district. Data collection techniques through observation, interviews and documentation. The data analysis used qualitative descriptive analysis techniques. The results show that in this megengan tradition it is used to pray for the elders, the ancestors of the grave experts who have preceded us, and as an expression of gratitude because they are still given a long healthy life and afiat can still meet in the holy month of Ramadan, by bathing in kramas to purify Then a feast is held by exchanging apem (snacks) to welcome fasting, which comes from the Javanese po-so which means Ngeposne Roso (resting the world's happy and sad), these are the values of direct education.